Photovoltaic system performance improvement by applying enhanced incremental conductance algorithm - Andriva Putri, Yuni; Asnil (Department of Electrical Engineering Universitas Negeri Padang, 2024)
This research aims to optimize the performance of a photovoltaic system using the Incremental Conductance algorithm (INC). The incremental conductance method is susceptible to oscillations in the steady state and tracking accuracy under solar radiation variations. This research investigates how Incremental conductance can be modified to improve its performance in reducing oscillations and accelerating cycle speed. Tests were carried out at irradiation variations of 200, 400 and 600 W/m². The INC method produces conventional tracking times of 500 ms, 555 ms, and 300 ms with maximum power of 1.89 W, 5,542 W, and 8,232 W at increased irradiation. Meanwhile the INC modification method shows a significant improvement with tracking times of 345 ms, 330 ms, and 205 ms, producing maximum power of 2.73 W, 7.36 W, and 9.9 W. When reducing irradiation, the modification method achieves tracking times of 195 ms and 455 ms. These results show that the INC modification method is superior in reducing oscillations, speeding up tracking time, and producing higher maximum power so as to increase the overall efficiency of the photovoltaic system